Drought tolerance in MnSOD transgenic Hevea brasiliensis in a dry sub-humid environment - Sumesh, K.V.; Satheesh, P.R.; Sreelatha, S.; Ravichandran, S.; Thulaseedharan, A.; Jayashree, R.; Krishnakumar, R.; Annamalainathan, K.; Singh, Meena; Jacob, James (Journal of Plantation Crops, 2014)
One year old bud-grafted plants of MnSOD transgenic Hevea lines (L1 and L2) and an untransformed line of clone RRII 105 were used in the present study to evaluate their physiological performance in a dry sub-humid environment by withholding irrigation and to assess the recovery by re-watering. The dry matter partitioning was more towards the root in transgenic lines (55% and 60% in Ll and L2, respectively) but, was less in the untransformed RRII 105 (43%). After six days of moisture stress in polybags, pre-dawn leaf water potential and relative water content declined in all the lines, however, transgenic line L1 showed higher tissue water content throughout the drought as well as recovery period. Chlorophyll content did not show any significant reduction. Net photosynthetic rate (PN) declined rapidly and it reached near zero on the third day of drought imposition except for line L1, which showed lesser decline in PN. The decline in stomatal conductance (gs) was more rapid than PN in all the lines. On re-watering, recovery of PN and gs was better in the transgenic lines than untransformed RRII 105, which did not recover fully from the drought impact. Antioxidant enzymes, superoxide dismutase and peroxidase did not show a definite trend in their activities in these lines. However, it was found that the transgenic line L1 had better drought tolerant capacity in terms of lesser inhibition of photosynthetic rate under drought and faster recovery on re-watering.